PENERAPAN ICE BREAKING SEBAGAI SOLUSI UNTUK MENINGKATKAN FOKUS SISWA MADRASAH IBTIDAIYAH DALAM MENGHADAPI TANTANGAN PERUBAHAN PEMBELAJARAN ERA DIGITAL - Faizatul Widat; Ach. Mawazir Az Zamzami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to apply the impact of applying the icebreaking technique in increasing the focus and involvement of Madrasah Ibtidaiyah (MI) Al Islamiyah students, especially in facing learning challenges in the digital era. The method used is a qualitative approach with a case study design, which includes in-depth interviews, participatory observation, and distributing questionnaires to students. The research results showed that the application of the icebreaking technique significantly increased student concentration, with 85% of students reporting feeling more prepared and focused in participating in learning after the icebreaking activity. Apart from that, the implementation of icebreaking also creates a more interactive and fun classroom atmosphere, which encourages active student involvement in both face-to-face and digital learning. Icebreaking techniques that integrate technology, such as the use of educational apps or games, have proven effective in helping students adapt to digital learning without being distracted by distractions from technological devices. However, the limitations of this research lie in its limited scope to one madrasa and not taking into account other external factors that influence student focus. Further research is recommended to expand the scope and consider external variables in the analysis.